Bovine Lactoferrin Stimulates Anchorage-Independent Cell Growth via Membrane-Associated Chondroitin Sulfate and Heparan Sulfate Proteoglycans in PC12 Cells - Toshiaki Ishii; Hiroshi Ishimori; Kaori Mori; Tomoka Uto; Kenji Fukuda; Tadasu Urashima; Masakazu Nishimura (Elsevier, 2007)
Bovine lactoferrin (bLf) is an iron-binding secretory protein present in breast milk, mucosal secretions, and the secondary granules of neutrophils. Although bLf has multiple functions, including antimicrobial and immunomodulatory activities, its effect on neuronal cells is not fully understood. We report that bLf prevents cell adhesion of PC12 cells and allows them to be cultivated in suspension. PC12 cells normally adhere well to plastic culture plates and show anchorage-dependent cell growth, but we found that soon after adding bLf, they detach from culture plates and begin to grow in suspension. When bLf was removed from the medium, the cells began to re-adhere to the plates. Thus, bLf inhibits cell adhesion and stimulates anchorage-independent growth in PC12 cells. On the other hand, bLf-induced cell suspension growth was not observed when cells were grown on a laminin matrix, suggesting that bLf does not affect integrin-mediated cell adhesion on a laminin matrix. Treatment of cells with heparin or chondroitin sulfate A or C inhibited bLf-induced growth in cell suspension. Furthermore, pretreatment of cells with heparinase and/or chondroitinase prevented direct binding of bLf to the cell membrane. These results suggest that bLf binds to the membrane of PC12 cells via membrane-associated proteoglycans and leads to anchorage-independent growth. Keywords:: bovine lactoferrin, cell adhesion, PC12 cell, proteoglycan, cell suspension